FAKTOR-FAKTOR YANG MEMENGARUHI RESPONSE TIME PETUGAS AMBULANS GAWAT DARURAT PADA KEJADIAN OHCA : Literature Review - Agatta Surya Wijaya (2020)
Out Hospital Cardiac Arrest (OHCA) is an emergency condition that is a condition of cardiac arrest which happened outside the hospital. The survival rate of OHCA patients can be influenced by the response time of the Emergency Ambulance officer. Several factors profoundly influence the response time of EMS officers. The purpose of this paper is to analyses the factors that influence the response time of the EMS team to OHCA events. The method in this paper is a literature review from existing research available in databases PubMed, Science Direct, and Google Scholar and search engines. Seven out of 609 articles are identified based on the inclusion criteria of the study and were eligible for review. The Results of the literature review study show: Three articles found that ability or skill, and duration of work is affected EMS Team response time in handling patients in the event of OHCA. Two other studies explained that weather or temperature and traffic jams influenced the response time, and another two articles showed that the ambulance system, the ambulance equipment, and the patient's condition are also factors that influence the response time of emergency ambulance officers in handling patients in the event of OHCA. Conclusion: the factors that influence the response time of EMS officers in OHCA events consist of ability or skill, duration of work, weather or temperature, traffic jams, the ambulance system, the ambulance equipment, and the patient's condition.